KONSEP BIDâAH HASANAH (Perpspektif Maqashid Al-Syathibi dan Ibnu âAsyur) - Anshari, Zaidan (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2018)
Bidâah is the classic issue but stil actual to be discussed. It is caused by the classification of bidâah term into two kinds still presents the polemic till this era. The different opinion about this concept is unsolved yet. Adherent of bidâah hasanah andÂ repellent of it have argument each other. Principle of their argument may comes from hadis perpective, sahabah perspective (attitude of sahabah), language perspective, and also ushul fiqh perspective. This perspective (ushul fiqh) is the most difficult instrument to understand the substance of hadis, especially the hadis which talk about bidâah. But there is the chapter of ushul fiqh which talk about the purpose of syariah, it called by maqashid syariah. From this perspective we can try to explain the concept of bidâah hasanah. There are two most popular theory of maqashid syariah from two figures of different period. Al-syathibi and Ibnu âAsyur, talk in detail of maqashid syariah. From their theory, the concept of bidâah hasanah can result the different view. Al-Syathibiâs theory refuses explicitly the concept of bidâah hasanah. Whereas in the Ibnu âAsyurâs theory of maqashid, this concept still has chances to be justified. This article will try to research this concept from these two perspectives.